2015
DOI: 10.1002/ls.1301
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the corrosion-wear behaviours of Hastelloy C276 alloy in seawater

Abstract: A systematic investigation has been carried out in the present work to study the electrochemical and corrosion-wear behaviours of Hastelloy C276 alloy sliding against Al 2 O 3 pin in artificial seawater, using a pin-on-disc tribometer integrated with a potentiostat for electrochemical control. It can be observed that the cathodic shift of open circuit potential and three order of magnitude increase of current density formed due to sliding. The total corrosion-wear loss increases with increasing applied potenti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 29 publications
1
14
0
Order By: Relevance
“…Interestingly, the sharp peaks in potential at 8761 and 9081 s coincide with an OCP surge and a decrease in COF, as marked by the interrupted vertical lines. These correlations suggest the discontinuous formation of third body particles by mechanical wear, a concept initially developed by Godet and adopted by other authors . Wear particles are detached from the first body (AISI 304 steel disc) leading to a sharp increase in the OCP due to oxidation of the fresh active steel surface exposed to the corrosive environment.…”
Section: Resultsmentioning
confidence: 81%
See 1 more Smart Citation
“…Interestingly, the sharp peaks in potential at 8761 and 9081 s coincide with an OCP surge and a decrease in COF, as marked by the interrupted vertical lines. These correlations suggest the discontinuous formation of third body particles by mechanical wear, a concept initially developed by Godet and adopted by other authors . Wear particles are detached from the first body (AISI 304 steel disc) leading to a sharp increase in the OCP due to oxidation of the fresh active steel surface exposed to the corrosive environment.…”
Section: Resultsmentioning
confidence: 81%
“…However, it should be noted that the OCP recovering time for the surface rubbed with the Electrolyte 1 is longer, indicating a slower regeneration of the passive films when compared to the surface rubbed with Electrolyte 2 . It has been reported that this cyclic depassivation–repassivation mechanism leads to wear accelerated corrosion . It can be seen that throughout the entire sliding period, the OCP fluctuates strongly in case of the surface rubbed with Electrolyte 1.…”
Section: Resultsmentioning
confidence: 93%
“…It is easy to observe that OCP stabilize at the value of about −0.7 V in initial 5‐minute stabilization. Once rubbing, the OCP abruptly shifts to the cathodic direction, which is usually explained by the destruction of the surface passive state . The increasing load would enlarge the degree of cathodic shift of OCP.…”
Section: Resultsmentioning
confidence: 99%
“…When rubbing is terminated after 25‐minute sliding, the OCP increases abruptly and returns the original OCP value (−0.7 V). This can be explained by the repassivation of the wear track without rubbing …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation